1990
DOI: 10.1038/ki.1990.107
|View full text |Cite
|
Sign up to set email alerts
|

Red cell trapping after ischemia and long-term kidney damage. Influence of hematocrit

Abstract: The influence of the hematocrit (Hct) on the trapping of red blood cells (RBC) in the renal microvasculature and its effect on the long-term outcome following unilateral ischemia were investigated in the rat. The results showed that an increase in the duration of ischemia increased the RBC trapping, as measured by 51Cr-labeled erythrocytes, in a dose-dependent manner. At normal Hct (46%) the period of ischemia producing half-maximum RBC trapping was 45 minutes, whereas after hemodilution (Hct = 31%) or hemocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 23 publications
4
36
0
Order By: Relevance
“…Other studies have demonstrated a regional variation of the hematocrit within the lung, and it is unclear whether the lung and peripheral hematocrits are equal (30,31). In this study, the lung hematocrit was estimated to 0.43 Ϯ 0.08 in the LPS group and to 0.55 Ϯ 0.06 in the control group, which reasonably agree with reported peripheral values of 0.45-0.50 in rats (32,33). However, the finding of a lower hematocrit in the LPS group disagrees with studies where the hematocrit was unaltered (31) or increased (34) after LPS challenge in rats.…”
Section: Rat Lung Spectroscopy Using Hyperpolarizedsupporting
confidence: 81%
“…Other studies have demonstrated a regional variation of the hematocrit within the lung, and it is unclear whether the lung and peripheral hematocrits are equal (30,31). In this study, the lung hematocrit was estimated to 0.43 Ϯ 0.08 in the LPS group and to 0.55 Ϯ 0.06 in the control group, which reasonably agree with reported peripheral values of 0.45-0.50 in rats (32,33). However, the finding of a lower hematocrit in the LPS group disagrees with studies where the hematocrit was unaltered (31) or increased (34) after LPS challenge in rats.…”
Section: Rat Lung Spectroscopy Using Hyperpolarizedsupporting
confidence: 81%
“…Previous studies have indicated that the RBC trapping occurs either during ischaemia [5,10] or in the very early recirculation phase [9,14], and disappears within less than 24 h [10,14]. It is evident from the results for the contra lateral intact kidneys in the present study that mannitol per se does not induce RBC trap ping.…”
Section: Discussionsupporting
confidence: 71%
“…28,29 Extensive trapping of erythrocytes was seen in the ISOM ( Figure 7B) and inner medulla ( Figure 7E) of saline-treated animals after 1-hour reperfusion after 45-minute ischemia. The trapping of erythrocytes was greatly reduced in ISOM ( Figure 7C) and the inner medulla ( Figure 7F) of SS-31 IR animals.…”
Section: Ss-31 Reduced Medullary Microvascular Congestionmentioning
confidence: 99%